Recent Development of Flax Fibres and Their Reinforced Composites Based on Different Polymeric Matrices - Zhu, Jinchun; Zhu, Huijun; Njuguna, James A. K.; Abhyankar, Hrushikesh (Cranfield University, 2013)
This work describes flax fibre reinforced polymeric composites with recent developments. The properties of flax fibres, as well as advanced fibre treatments such as mercerization, silane treatment, acylation, peroxide treatment and coatings for the enhancement of flax/matrix incompatibility are presented. The characteristic properties and characterizations of flax composites on various polymers including polypropylene (PP) and polylactic acid, epoxy, bio-epoxy and bio-phenolic resin are discussed. A brief overview is also given on the recent nanotechnology applied in flax composites. Keywords: flax composites; mechanical properties; modifications